Pengaruh Kemampuan Literasi Numerasi Terhadap Hasil Belajar Siswa Ditinjau Dari Kemampuan Berpikir Analogis Materi Aljabar Kelas VII - rumiati, lina_0802 (Jurnal Edumatic: Jurnal Pendidikan Matematika, 2025)
The research on the influence of numeracy literacy on students' learning outcomes viewed from their analogical thinking skills aims to: (1) determine whether there is an influence of numeracy literacy skills on learning outcomes, (2) determine whether there is an influence of analogical thinking skills on learning outcomes, and (3) determine whether there is an interaction between numeracy literacy skills and analogical thinking skills. This study employed a quantitative research method with a pretest-posttest control group design. The population consisted of 60 students, and the sample comprised 60 students, specifically 30 students from Class VIIA and 30 students from Class VIIB. The research was conducted at SMPN 3 Paron. Sampling was carried out using the cluster sampling technique. Data collection techniques included an analogical thinking test, an algebra material test for the pretest, and an algebra material test incorporating numeracy literacy for the posttest. Data analysis was conducted using two-way ANOVA at a significance level of 0.05. The results of the study are as follows: (1) There is a significant influence of numeracy literacy skills on learning outcomes, with a significance level of 0.005 < 0.05. (2) There is a significant influence of analogical thinking skills on students' learning outcomes, with a significance level of 0.041 < 0.05. (3) There is no significant interaction between students' numeracy literacy skills and their analogical thinking skills, with a significance level of 0.154 > 0.05.